RUBEM BRAGRA: INTERTEXTUALIDADE E SOCIEDADE - Tchiago Inague Rodrigues; Édima de Souza Mattos (Universidade do Oeste Paulista, 2010)
It is important to research the intertextual and dialogical relations of different literary-aesthetic manifestation between them, notably the journalistic text and the literature.This article has as object of study the chronicles of Rubem Braga, jornalist and writer who was noted for only produce texts of this hybrid genre.The elected body of the research is the chronicle ''O jovem casal'' (1953), which is made a critical-interpretive analysis.Highlights how the social issues of the period were exposed, revealing the critical role of the intellectual in front of his time's society.